The gulf : a novel - Boggs, Belle (Graywolf Press, 2019)
Marianne is in a slump: barely able to support herself by teaching, not making progress on her poetry, about to lose her Brooklyn apartment. When her novelist ex-fiancé, Eric, and his venture capitalist brother, Mark, offer her a job directing a low-residency school for Christian writers at a motel they've inherited on Florida's Gulf Coast, she can't come up with a reason to say no. The Genesis Inspirational Writing Ranch is born, and liberal, atheist Marianne is soon knee-deep in applications from writers whose political and religious beliefs she has always opposed but whose money she's glad to take. Janine is a schoolteacher whose heartfelt poems explore the final days of Terri Schiavo's life. Davonte is a former R&B superstar who hopes to reboot his career with a bestselling tale of excess and redemption. Lorraine and Tom, eccentric writers in need of paying jobs, join the Ranch as instructors.